Electrocatalytic reducing agent with core-shell structure and preparation method thereof

By adopting an Sn-Ti core-shell structure electrocatalyst with a core-shell structure, the problems of poor stability and low selectivity of the catalyst in the catalytic reduction reaction in the prior art are solved, and efficient and stable CO2 reduction effect is achieved.

CN115491714BActive Publication Date: 2025-04-08SOUTH CHINA NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211175194.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-26
Publication Date
2025-04-08
Estimated Expiration
2042-09-26

AI Technical Summary

Technical Problem

The prior art has problems of poor catalyst stability and low selectivity in the catalytic reduction reaction of carbon dioxide.

Method used

An electrocatalytic reducing agent with a core-shell structure is used, and the preparation method includes using polystyrene nanospheres as templates, impregnating the precursor liquid of tin and titanium ions, and obtaining the Sn-Ti core-shell structure electrocatalyst through vacuum filtration and calcination steps.

Benefits of technology

It improves the stability and selectivity of electrocatalytic CO2 reduction, achieves high catalytic activity and long life, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115491714B_ABST
    Figure CN115491714B_ABST
Patent Text Reader

Abstract

The invention discloses an electrocatalytic reducing agent with a core-shell structure and a preparation method thereof, the method comprising: providing polystyrene nanospheres and a precursor solution, wherein the precursor solution contains tin ions and titanium ions; immersing the polystyrene nanospheres in the precursor solution, then vacuum filtering, and calcining the solid obtained after the filtration to obtain the electrocatalytic reducing agent with a core-shell structure. The energy efficiency, life span and stability of CO2 electroreduction are improved by synthesizing a three-dimensional ordered mesoporous Sn-Ti core-shell structure using polystyrene as a template. The method first synthesizes polystyrene nanospheres by a soap-free emulsion method, then impregnates the polystyrene nanospheres with Sn and Ti precursor solutions, and finally performs a two-step step calcination in air to obtain a Sn-Ti core-shell structure compound. Through physicochemical characterization, the Sn-Ti core-shell structure catalyst exhibits extremely high catalytic selectivity and stability at the optimal potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrocatalytic reducing agent preparation, and in particular to an electrocatalytic reducing agent with a core-shell structure and a preparation method thereof. Background Art

[0002] Electrochemical reduction of carbon dioxide (CO2) is a leading research field that can be used not only for CO2 utilization, but also for the production of green fuels and storage of renewable energy (solar or wind energy). In this process, CO2 can be reduced to carbonaceous compounds such as carbon monoxide, methane, formic acid, acetic acid and ethanol, but existing technologies still have problems such as poor selectivity of CO2 reduction products, poor stability of catalyst materials, kinetic obstacles, and low selectivity for specific products.

[0003] Therefore, the prior art needs to be further improved and enhanced. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide an electrocatalytic reducing agent with a core-shell structure and a preparation method thereof, aiming to solve the problems of poor stability and low selectivity of the existing electrocatalysts used in the catalytic reduction reaction of carbon dioxide.

[0005] A method for preparing an electrocatalytic reducing agent having a core-shell structure, comprising the following steps:

[0006] Providing polystyrene nanospheres and a precursor solution, wherein the precursor solution contains tin ions and titanium ions;

[0007] The polystyrene nanospheres are immersed in the precursor solution, and then vacuum filtered, and the solid obtained after the filtration is calcined to obtain the electrocatalytic reducing agent with a core-shell structure.

[0008] Optionally, in the method for preparing the electrocatalytic reducing agent with a core-shell structure, the calcination temperature is 400-1000°C.

[0009] Optionally, the method for preparing the electrocatalytic reducing agent having a core-shell structure, wherein the step of calcining the solid obtained after suction filtration to obtain the electrocatalytic reducing agent having a core-shell structure specifically comprises:

[0010] The temperature is raised to 400° C. at a heating rate of 1-3° C. / min and calcined for 1-2 hours, and then the temperature is raised to 1000° C. at a heating rate of 4-6° C. / min and calcined for 1-2 hours to obtain an electrocatalytic reducing agent with a core-shell structure.

[0011] Optionally, in the method for preparing the electrocatalytic reducing agent with a core-shell structure, the molar ratio of tin ions to titanium ions in the precursor solution is 0.6:1.4.

[0012] Optionally, in the method for preparing the electrocatalytic reducing agent with a core-shell structure, the preparation of the polystyrene nanospheres comprises the following steps:

[0013] Add polyvinyl pyrrolidone to deionized water, heat and stir to obtain a polyvinyl pyrrolidone solution;

[0014] The styrene monomer is dispersed in the polyvinyl pyrrolidone solution, and then a potassium persulfate solution is added to the polyvinyl pyrrolidone solution to carry out a polymerization reaction. After the reaction is completed, the polystyrene nanospheres are obtained by centrifugation and drying.

[0015] Optionally, in the method for preparing the electrocatalytic reducing agent having a core-shell structure, the preparation of the precursor solution comprises:

[0016] Adding stannous chloride and butyl titanate into anhydrous ethanol to obtain a mixed solution;

[0017] Hydrochloric acid is added dropwise to the mixed solution to obtain the precursor solution.

[0018] Optionally, in the method for preparing the electrocatalytic reducing agent with a core-shell structure, the molar concentration of the potassium persulfate solution is 0.6-0.8 mM / L.

[0019] An electrocatalytic reducing agent with a core-shell structure, wherein the electrocatalytic reducing agent is prepared by the above-mentioned preparation method.

[0020] Optionally, the electrocatalytic reducing agent having a core-shell structure has an ordered mesoporous core-shell structure.

[0021] Beneficial effects: Compared with the prior art, the preparation method of the electrocatalytic reducing agent with a core-shell structure provided by the present invention not only has a simple synthesis method and strong operability, but also has high efficiency and stability in electrocatalytic CO2 reduction, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The scanning electron microscope images of the three-dimensional ordered mesoporous Sn-Ti core-shell structure in Example 1; wherein (a) indicates that the three-dimensional ordered mesoporous Sn-Ti core-shell structure has a long-range ordered porous structure without cracks and structural collapse; (b) indicates that the pore structure exhibits a two-dimensional hexagonal structure, and the pore size distribution is uniform, and the pore size is about 200nm, which is slightly smaller than the diameter of the polystyrene sphere; (c) shows uniformly distributed Ti and Sn;

[0023] Figure 2 The electrocatalytic activity and selectivity data of the three-dimensional ordered mesoporous Sn-Ti core-shell structure in Example 1; wherein (a) indicates that the three-dimensional ordered mesoporous Sn-Ti core-shell structure material has a larger current response under a wider electrochemical window; (b) indicates that the selectivity of the three-dimensional ordered mesoporous Sn-Ti core-shell structure for CO reaches about 96% at a potential of -0.54 V (Vs.RHE);

[0024] Figure 3 The three-dimensional ordered mesoporous Sn-Ti core-shell structure prepared in Example 1 is used as the electrocatalytic CO2 stability data. DETAILED DESCRIPTION

[0025] The present invention provides an electrocatalytic reducing agent with a core-shell structure and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0026] In order to solve the problems of poor stability and low selectivity of the existing electrocatalysts used in the catalytic reduction reaction of carbon dioxide, this embodiment provides a method for preparing an electrocatalytic reducing agent with a core-shell structure, comprising the following steps:

[0027] S10, providing polystyrene nanospheres and a precursor solution, wherein the precursor solution contains tin ions and titanium ions;

[0028] S20, soaking the polystyrene nanospheres in the precursor solution, then vacuum filtering, and calcining the solid obtained after the filtration to obtain the electrocatalytic reducing agent with a core-shell structure.

[0029] In this embodiment, the polystyrene nanospheres have the characteristics of small particle size, large specific surface area, strong adsorption capacity, good dispersibility, low cost, etc., and can effectively control the average particle size. Using polystyrene nanospheres as templates, they are then impregnated with a precursor solution containing tin ions and titanium ions, and then calcined in air to obtain a Sn-Ti core-shell structure electrocatalytic reducing agent with a core of tin-titanium alloy and a shell of titanium. The Ti atoms in the shell protect the tin atomic structure and three-dimensional ordered skeleton, thereby extending the life of the catalyst. The Sn-Ti core-shell structure catalyst achieves a compromise between the nano-agglomeration level dispersion of the Sn-based metal at the active site and the structural stability, and has a robust structure-activity relationship. In other words, because the core-shell structure can simultaneously maintain the activity and stability of the catalyst. The shell can protect the internal metal core and improve the stability of the catalyst; and the outer particle layer is evenly dispersed on the metal core, providing more active sites and improving the performance of the catalyst.

[0030] In one implementation of this embodiment, the polystyrene nanospheres can be synthesized by a soap-free emulsion method, specifically, polyvinyl pyrrolidone can be dissolved in deionized water, heated and stirred, and kept warm. Styrene monomer is then added, and finally a certain amount of potassium persulfate aqueous solution is added to perform a polymerization reaction. After the reaction is complete, the polystyrene nanospheres are obtained by centrifugation and drying to obtain a tightly packed array.

[0031] In this embodiment, the precursor solution can be SnCl2 and C16H 36 O4Ti is used as the corresponding Sn and Ti metal salts, anhydrous ethanol is used as the solvent, and HCl is added dropwise to inhibit the hydrolysis of the metal salts, and finally a clear precursor solution is obtained. 36 The O4Ti concentrations were controlled at 0.6 and 1.4 M according to the corresponding molar ratios.

[0032] In this embodiment, the polystyrene nanospheres impregnated with the precursor solution are vacuum filtered and calcined in two stages in the air to remove the template (polystyrene nanospheres). Exemplarily, the temperature is raised to 400°C for calcination for 1-2 hours at a heating rate of 1-3°C / min, and then the temperature is raised to 1000°C for calcination for 1-2 hours at a heating rate of 4-6°C / min, and the template is removed to obtain an electrocatalytic reducing agent with a core-shell structure. The particle size can be made more uniform and the particles more regular by calcining in stages. Because a large amount of intermediate phases are produced while heating and decomposing, a large amount of heat energy is generated in the reaction system. A large amount of heat causes the temperature to rise rapidly in a relatively short period of time, local materials melt, and a large number of crystal nuclei are instantly produced. If the furnace temperature is raised to the set reaction temperature in a short time at this time, the high heat generated will not have time to be evenly absorbed, which will cause some crystal nuclei to grow and crystallize instantly, resulting in uneven product particle size.

[0033] Based on the same inventive concept, the present invention also provides an electrocatalytic reducing agent with a core-shell structure, wherein the electrocatalytic reducing agent is prepared by the above-mentioned preparation method. The electrocatalytic reducing agent has an ordered mesoporous core-shell structure, that is, a three-dimensional mesoporous Sn-Ti core-shell structure.

[0034] In this embodiment, the ordered porous structure provides a higher local alkaline environment, improves the selectivity of CO, and broadens the limit of the potential window. The prepared Sn-Ti core-shell structure material significantly improves the CO2 reduction overpotential, CO selectivity, and Faraday efficiency through structural and surface electronic reconstruction during the CO2 reduction process, providing a guiding direction for the material design of high-performance CO2 electrocatalytic reducers, which has positive significance for industrial-scale production.

[0035] Example 1

[0036] The first step is the preparation of polystyrene nanospheres

[0037] First, 5.0 g of polyvinyl pyrrolidone (PVP, Mw = 58000) was dissolved in 400 mL of deionized water and heated with stirring, and the temperature was maintained at 60°C. Subsequently, 50 mL of styrene monomer was added to the above PVP solution. Finally, 80 mL of 0.6 mM potassium persulfate aqueous solution was slowly added dropwise to the above mixed solution and polymerized for 24 hours. After the reaction was complete, centrifugation and drying were performed to obtain a tightly packed array of polystyrene nanospheres.

[0038] The second step is to prepare the metal Sn and Ti precursor solutions

[0039] SnCl2 and C16H 36 O4Ti was used as the metal salt, 6 mL of anhydrous ethanol was used as the solvent, and HCl was added dropwise to inhibit the hydrolysis of the metal salt, and finally a clear precursor solution was obtained. 36 The O4Ti concentrations were controlled at 0.6 and 1.4 M, respectively.

[0040] The third step is to prepare three-dimensional ordered mesoporous Sn-Ti core-shell structure

[0041] The polystyrene nanospheres were immersed in Sn and Ti precursor solutions for 4 hours, and the excess precursor solution was removed by vacuum filtration. The temperature was raised to 400°C at 1°C / min and kept for 2 hours. Then, the temperature was raised to 800°C at 4°C / min and kept for 2 hours to obtain the target product. The SEM image of the prepared three-dimensional ordered mesoporous Sn-Ti core-shell structure is shown in Figure 2. Figure 1 As shown. Figure 1 (a) It can be seen that the three-dimensional ordered mesoporous Sn-Ti core-shell structure has a long-range ordered porous structure without cracks and structural collapse. Figure 1 The pore structure of (b) shows a two-dimensional hexagonal structure with uniform pore size distribution. The pore diameter is about 200 nm, which is slightly smaller than the diameter of the polystyrene sphere. Figure 1 (c) shows uniform distribution of Ti and Sn. Figure 2 , Electrocatalytic performance of three-dimensional ordered mesoporous Sn-Ti core-shell structure materials in H-type electrochemical cells. Figure 2 (a) It can be seen that the material has a large current response in a wide electrochemical window and exhibits excellent activity. Figure 2 In (b), the selectivity of the three-dimensional ordered mesoporous Sn-Ti core-shell structure for CO reaches about 96% at a potential of -0.54V (Vs.RHE). As shown in Figure 3a, the prepared three-dimensional ordered mesoporous Sn-Ti core-shell structure electrode has no obvious attenuation after continuous electrolysis for 160 hours, and has good stability. At the same time, the Faraday efficiency of CO is maintained at about 95%, achieving efficient conversion of CO2.

[0042] Example 2

[0043] The first step is the preparation of polystyrene nanospheres

[0044] First, 5.0 g of polyvinyl pyrrolidone (PVP, Mw = 58000) was dissolved in 400 mL of deionized water and heated with stirring, and the temperature was maintained at 60°C. Subsequently, 50 mL of styrene monomer was added to the above PVP solution. Finally, 80 mL of 0.7 mM potassium persulfate aqueous solution was slowly added dropwise to the above mixed solution and polymerized for 24 hours. After the reaction was complete, centrifugation and drying were performed to obtain a tightly packed array of polystyrene nanospheres.

[0045] The second step is to prepare the metal Sn and Ti precursor solutions

[0046] SnCl2 and C16H 36 O4Ti was used as the metal salt, 6 mL of anhydrous ethanol was used as the solvent, and HCl was added dropwise to inhibit the hydrolysis of the metal salt, and finally a clear precursor solution was obtained. 36 The O4Ti concentrations were controlled at 0.6 and 1.4 M, respectively.

[0047] The third step is to prepare three-dimensional ordered mesoporous Sn-Ti core-shell structure

[0048] The polystyrene nanospheres were immersed in Sn and Ti precursor solutions for 4 hours. After the excess precursor solution was removed by vacuum filtration, the temperature was increased to 400°C at 2°C / min and kept for 2 hours. Subsequently, the temperature was increased to 700°C at 5°C / min and kept for 2 hours to obtain the target product.

[0049] Example 3

[0050] The first step is the preparation of polystyrene nanospheres

[0051] First, 5.0 g of polyvinyl pyrrolidone (PVP, Mw = 58000) was dissolved in 400 mL of deionized water and heated with stirring, and the temperature was maintained at 60°C. Subsequently, 50 mL of styrene monomer was added to the above PVP solution. Finally, 80 mL of 0.8 mM potassium persulfate aqueous solution was slowly added dropwise to the above mixed solution and polymerized for 24 hours. After the reaction was complete, centrifugation and drying were performed to obtain a tightly packed array of polystyrene nanospheres.

[0052] The second step is to prepare the metal Sn and Ti precursor solutions

[0053] SnCl2 and C16H 36 O4Ti was used as the metal salt, 6 mL of anhydrous ethanol was used as the solvent, and HCl was added dropwise to inhibit the hydrolysis of the metal salt, and finally a clear precursor solution was obtained. 36 The O4Ti concentrations were controlled at 0.6 and 1.4 M, respectively.

[0054] The third step is to prepare three-dimensional ordered mesoporous Sn-Ti core-shell structure

[0055] The polystyrene nanospheres were immersed in Sn and Ti precursor solutions for 4 hours. After the excess precursor solution was removed by vacuum filtration, the temperature was increased to 400°C at 2°C / min and kept for 2 hours. Subsequently, the temperature was increased to 900°C at 5°C / min and kept for 2 hours to obtain the target product.

[0056] Example 4

[0057] The first step is the preparation of polystyrene nanospheres

[0058] First, 5.0 g of polyvinyl pyrrolidone (PVP, Mw = 58000) was dissolved in 400 mL of deionized water and heated with stirring, and the temperature was maintained at 60°C. Subsequently, 50 mL of styrene monomer was added to the above PVP solution. Finally, 80 mL of 0.8 mM potassium persulfate aqueous solution was slowly added dropwise to the above mixed solution and polymerized for 24 hours. After the reaction was complete, centrifugation and drying were performed to obtain a tightly packed array of polystyrene nanospheres.

[0059] The second step is to prepare the metal Sn and Ti precursor solutions

[0060] SnCl2 and C16H 36 O4Ti was used as the metal salt, 6 mL of anhydrous ethanol was used as the solvent, and HCl was added dropwise to inhibit the hydrolysis of the metal salt, and finally a clear precursor solution was obtained. 36 The O4Ti concentrations were controlled at 0.6 and 1.4 M, respectively.

[0061] The third step is to prepare three-dimensional ordered mesoporous Sn-Ti core-shell structure

[0062] The polystyrene nanospheres were immersed in Sn and Ti precursor solutions for 4 hours. After the excess precursor solution was removed by vacuum filtration, the temperature was increased to 400°C at 3°C / min and kept for 2 hours. Subsequently, the temperature was increased to 1000°C at 6°C / min and kept for 2 hours to obtain the target product.

[0063] In summary, the present invention provides an electrocatalytic reducing agent with a core-shell structure and a preparation method thereof, the method comprising: providing polystyrene nanospheres and a precursor solution, the precursor solution containing tin ions and titanium ions; soaking the polystyrene nanospheres in the precursor solution, then vacuum filtering, and calcining the solid obtained after filtration to obtain the electrocatalytic reducing agent with a core-shell structure. The energy efficiency, life and stability of CO2 electroreduction are improved by synthesizing a three-dimensional ordered mesoporous Sn-Ti core-shell structure using polystyrene as a template. The method first synthesizes polystyrene nanospheres by a soap-free emulsion method, then impregnates the polystyrene nanospheres with Sn, Ti precursor solutions, and finally performs a two-step step calcination in air to obtain a Sn-Ti core-shell structure compound. Through physicochemical characterization, the Sn-Ti core-shell structure catalyst exhibits extremely high catalytic selectivity and stability at the optimal potential. The three-dimensional ordered mesoporous Sn-Ti core-shell structure provided by the present invention not only has a simple synthesis method and strong operability, but also has high efficiency and stability in electrocatalytic CO2 reduction, and has broad application prospects.

[0064] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing an electrocatalytic reducing agent having a core-shell structure, characterized in that: The steps include: Providing polystyrene nanospheres and a precursor solution, wherein the precursor solution contains tin ions and titanium ions; Soaking the polystyrene nanospheres in the precursor solution, then vacuum filtering, and calcining the solid obtained after the filtration to obtain the electrocatalytic reducing agent with a core-shell structure; The step of calcining the solid obtained after suction filtration to obtain an electrocatalytic reducing agent having a core-shell structure specifically comprises: The temperature is raised to 400° C. at a heating rate of 1-3° C. / min and calcined for 1-2 hours, and then the temperature is raised to 1000° C. at a heating rate of 4-6° C. / min and calcined for 1-2 hours to obtain an electrocatalytic reducing agent with a core-shell structure; The molar ratio of tin ions to titanium ions in the precursor solution is 0.6:1.4; The preparation of the precursor solution comprises: Adding stannous chloride and butyl titanate into anhydrous ethanol to obtain a mixed solution; Hydrochloric acid is added dropwise to the mixed solution to obtain the precursor solution.

2. The method for preparing the electrocatalytic reducing agent with a core-shell structure according to claim 1, characterized in that: The preparation of the polystyrene nanospheres comprises the following steps: Add polyvinyl pyrrolidone to deionized water, heat and stir to obtain a polyvinyl pyrrolidone solution; The styrene monomer is dispersed in the polyvinyl pyrrolidone solution, and then a potassium persulfate solution is added to the polyvinyl pyrrolidone solution to carry out a polymerization reaction. After the reaction is completed, the polystyrene nanospheres are obtained by centrifugation and drying.

3. The method for preparing the electrocatalytic reducing agent with a core-shell structure according to claim 2, characterized in that: The substance concentration of the potassium persulfate solution is 0.6-0.8 mM / L.

4. An electrocatalytic reducing agent having a core-shell structure, characterized in that: The electrocatalytic reducing agent is prepared by the preparation method described in any one of claims 1 to 3.

5. The electrocatalytic reducing agent with a core-shell structure according to claim 4, characterized in that: The electrocatalytic reducing agent has an ordered mesoporous core-shell structure.

Citation Information

Patent Citations

  • Photocatalyst for carbon dioxide reduction and preparation method and application thereof

    CN114931949A